Macroeconomics performance and economic growth in Japan - Law, Hien Yi (Universiti Malaysia Sarawak (UNIMAS), 2010)
This study empirically examines the relationship among macroeconomic performance (export, FDI, government expenditure) and economic growth in Japan. The time series data from years 1970 until year 2008 are used in this study.